The Effect of Mutation and Motivation on Employee Performance with Job Satisfaction as a Mediation Variable in the Kendal District Court - Dina Dwi Mastuti; Tristiana Rijanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
The purpose of this study is to analyze the influence of mutation and motivation on employee performance with job satisfaction as a mediation variable in the Kendal district court. This study uses a quantitative method. The sample in this study is 60 employees of the Kendal District Court.The sample determination technique in this study uses saturated sampling. Data analysis used multiple linear regression. The results of this study show that Mutation and Motivation have an effect on job satisfaction, Mutation and Job Satisfaction have a positive effect on employee performance, while Motivation has no effect on employee performance, Job satisfaction is able to mediate the effect of mutation and motivation on employee performance.